Semicondutores CuCrO2 e CuCr2O4 e seus compósitos formados com argila bentonita como fotocatalisadores na degradação do azocorante Tartrazina. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Azo dyes are among the most notorious and dangerous environmental pollutants due to their recalcitrant properties and potential for the formation of toxic products. The Tartrazina azo dye is a widely used food, which has been arousing interest due to its toxicity. In the search for more efficient methods of degradation of these compounds, alternative processes have been studied, among them the Advanced Oxidation Processes, which are based on the generation of hydroxyl radical (HO•), with high oxidant power. In this work, the Heterogeneous Photocatalysis process was used, known for its high efficiency in the degradation of hazardous compounds. In view of the great demand for the development of efficient materials for the application in photocatalytic processes, the objective of this work was to synthesize photocatalysts and study its efficiency in the face of the degradation of Tartrazine by heterogeneous photocatalysis. In this study, the semiconductors CuCrO2 and CuCr2O4 were synthesized by the self-combustion method that was rapid and efficient. Semiconductors were characterized elucidating aspects about their crystalline structure, morphology, composition, purity, light absorption and bandgap energy. However, one of the main limitations of the photocatalysis process is the separation and reuse of the photocatalyst at the end of the process, when these used in the form of dust. To work around this problem, semiconductors were immobilized in the bentonite clay matrix in order to tablet form that were made from the pressing of the material and could be reused by several cycles maintaining efficiency. In these composites the semiconductors were impregnated on the surface of the bentonite clay, without affecting its crystalline structure. The impregnation in clay did not significantly affect the bandgap values of the materials. The formation of composites resulted in materials with larger surface areas, higher pore volume and lower recombination rate of electron-hole pairs. Thus, synergism between the properties of semiconductors and clay generated an improvement in the photoactivity of composites formed with clay in relation to individual semiconductors. With 1 g of CuCrO2/clay composite in tablet form, an efficiency of 98.12% was obtained in the degradation of Tartrazine at pH 9 after 120 minutes of UV irradiation. For 1 g of CuCr2O4/clay composite, the efficiency of 99.73% was obtained in the degradation of Tartrazine at pH 3 with 120 minutes of visible light irradiation. The studies of photolysis and adsorption showed that these processes exert little influence on dye removal, and photocatalysis is the main mechanism. The study of active species showed that HO• radicals play a major role in the degradation of Tartrazine. Finally, studies were conducted to determine phenols, aromatic amines and toxicity tests of degraded samples. The initial dye sample showed phytotoxicity and ecotoxicity. The degraded samples using the Composites CuCrO2/clay and CuCr2O4/clay did not present phytotoxicity in front of the Lactuca sativa organism. The sample degrades with CuCrO2/clay composite showed no ecotoxicity, but the degraded sample using CuCr2O4/clay composite showed an increase in toxicity in relation to the body Daphnia magna.
Keywords: Azocorantes; Tartrazina; Fotocatálise Heterogênea; Semicondutores de Cromo e Cobre; Argila bentonita; Azo dyes; Tartrazine dye; Heterogeneous Photocatalysis; Chromium and Copper Semiconductors; Bentonite Clay; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA